2014
DOI: 10.1016/j.combustflame.2014.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Heat release rate markers for premixed combustion

Abstract: a b s t r a c tThe validity of the commonly used flame marker for heat release rate (HRR) visualization, namely the rate of the reaction OH + CH 2 O , HCO + H 2 O is re-examined. This is done both for methane-air and multicomponent fuel-air mixtures for lean and stoichiometric conditions. Two different methods are used to identify HRR correlations, and it is found that HRR correlations vary strongly with stoichiometry. For the methane mixture there exist alternative HRR markers, while for the multi-component f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 24 publications
3
44
0
Order By: Relevance
“…This is evident from significant Note that there are no signs of localized flame extinction in case C in spite of large values of the Karlovitz number (i.e., Ka > 100). This is consistent with several previous DNS findings [30][31][32][33]. The above discussion suggests that distinctly different physical mechanisms are likely to govern the behavior of invariants in the three cases considered.…”
Section: Selected Regions Of Instantaneous Nondimensional Temperaturesupporting
confidence: 81%
“…This is evident from significant Note that there are no signs of localized flame extinction in case C in spite of large values of the Karlovitz number (i.e., Ka > 100). This is consistent with several previous DNS findings [30][31][32][33]. The above discussion suggests that distinctly different physical mechanisms are likely to govern the behavior of invariants in the three cases considered.…”
Section: Selected Regions Of Instantaneous Nondimensional Temperaturesupporting
confidence: 81%
“…Regions of HRR are well predicted by the OH and CH 2 O concentrations, representative of the pixel-by-pixel product of the OHand CH 2 O-PLIF signals, in MILD and conventional non-premixed kerosene flames. This technique performs particularly well, in agreement with [38], at high rates of strain where peak HRR rates are large. This suggests that the experimental technique is a valid indicator of HRR for non-premixed kerosene spray flames.…”
Section: Discussionsupporting
confidence: 64%
“…This method would be valid as an experimental HRR marker only if laminar flame calculations show that the overlap of OH and CH 2 O mimics the local reaction zone. Such markers for HRR under MILD conditons have been discussed by Sidey and Mastorakos [6] for non-premixed methane counterflow flames with hot combustion product oxidiser and for methane and multi-fuel premixed systems by Minamoto and Swaminathan [37] and Nikolaou and Swaminathan [38]. Sidey and Mastorakos reported that the overlap of CH 2 O and OH was a good marker for the peak HRR location in MILD flames, in agreement with Minamoto and Swaminathan [37], although CH 2 O alone may offer a better correlation at higher rates of strain in CH 4 flames.…”
Section: Introductionmentioning
confidence: 99%
“…as an indicator. The R6 reaction is also re-examined and studied in the methane-air and multi component fuel-air mixture based on the elementary reactions analysis in (Nikolaou et al 2014) and the performance in the multi component fuel flame is emphasized. Inspired by the above idea, the study also proposes new multiple-kind HRIs based on the major species mentioned in Table 2.…”
Section: Analysis Of the Elementary Reactions And Evaluation Of Diffementioning
confidence: 99%